Literatur Review: Analysis of Health Effect of Microplastic Exposure The Aquatic Environment - Martha, Ardhya Farisha (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2025)
Background: Microplastics are extremely small plastic particles that are now widely found in aquatic environments and have entered the human food chain. This contamination raises serious concerns, as microplastics have the potential to carry toxic chemicals and cause various health disorders. Methods: This study employed a literature review method guided by the PRISMA model. Data sources were obtained from scientific articles published between 2020 and 2025 through databases such as Google Scholar, Garuda Journal, and PubMed. Results: Findings indicate that microplastics have been detected in fish, shellfish, shrimp, and even human feces. The dominant types include fibers, fragments, films, and foams, containing polymers such as PTFE, polycarbonate, and nylon. Reported health effects include digestive disorders, chronic inflammation, hematological disturbances (elevated leukocyte counts, decreased hemoglobin levels), and hormonal imbalances due to plastic additives acting as endocrine disruptors. Long-term exposure has been associated with damage to the liver, kidneys, and nervous system, as well as an increased risk of chronic diseases and cancer. Conclusions: Microplastics are not merely an environmental issue but also a tangible threat to human health. Scientific evidence indicates potential disruptions to the digestive, immune, hormonal, and metabolic systems resulting from repeated exposure.